2016
DOI: 10.1016/j.ijscr.2015.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid leakage from the umbilicus: Case report and literature review

Abstract: HighlightsNumerous abdominal complications have been reported in the literature.An umbilical cerebrospinal fluid (CSF) fistula following a VP shunt is an extremely rare complication.The mechanism of CSF leakage from the umbilicus is exactly unknown, we aimed to explain this mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…These include catheter perforation through the umbilicus, entering an umbilical hernia, or creating a CSF fistula through the umbilicus. [2][3][4][5][6][7][8][9][10] In each of these cases, the shunt was outside the body, adherent to the umbilicus, trapped in an umbilical hernia, or infected due to a fistula causing a CSF leak. Our cases are unique because the performance of our patients' VP shunts improved once their umbilical hernias were repaired without any of the reported causes of VP shunt malfunction involving the umbilicus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include catheter perforation through the umbilicus, entering an umbilical hernia, or creating a CSF fistula through the umbilicus. [2][3][4][5][6][7][8][9][10] In each of these cases, the shunt was outside the body, adherent to the umbilicus, trapped in an umbilical hernia, or infected due to a fistula causing a CSF leak. Our cases are unique because the performance of our patients' VP shunts improved once their umbilical hernias were repaired without any of the reported causes of VP shunt malfunction involving the umbilicus.…”
Section: Discussionmentioning
confidence: 99%
“…Dolas et al suggested that sterile inflammation caused softening of the tissue around an umbilicus without obvious hernia, leading to CSF fistula. 5 In two reported cases of umbilical CSF fistulas in children, umbilical hernias were believed to be contributing factors in the formation of the fistula, and the authors emphasized that the hernia must be repaired to successfully treat the fistula. 2 Another study reported that umbilical hernias increase the risk of CSF fistula formation or shunt catheter extrusion through the umbilicus and even recommended trying to repair the umbilical hernia before shunt placement if possible.…”
Section: Discussionmentioning
confidence: 99%
“…39 CSF umbilical fistula is more frequent than that of the trans-umbilical extrusion of the distal VPS catheter. [40][41][42][43]…”
Section: Discussionmentioning
confidence: 99%
“…However, many previous studies have considered the umbilicus to be an area of anatomical and congenital weakness (a Locus Minori Resistantiae ) that predisposes the patient to external migration of the VPS distal catheter or formation of CSF umbilical fistula resulting from a patent vitello‐intestinal duct or urachal remnant (Das et al, ; Gupta et al, ; Mohindra et al, ; Kella et al, ; Ardalan et al, ). Other studies have suggested that VPS extrusion through the umbilicus is simply due to an inflammatory process that softens the tissues causing CSF leakage and catheter extrusion (Eser et al, ; Fleissig et al, ; Dolas et al, ).…”
Section: Discussionmentioning
confidence: 99%